2015
DOI: 10.1039/c5ta06238a
|View full text |Cite
|
Sign up to set email alerts
|

Dual-functional semiconductor-decorated upconversion hollow spheres for high efficiency dye-sensitized solar cells

Abstract: Upconversion/semiconductor submicron hollow spheres composed of inner Na x GdF y O z :Yb/Er shell and outer TiO 2 shell (denoted Na x GdF y O z :Yb/Er@TiO 2 ) were, for the first time, crafted by exploiting colloidal carbon spheres as the scaffold. The hollow spheres were then incorporated into the TiO 2 nanoparticle film photoanode to yield dye-sensitized solar cells (DSSCs) with improved performance. The implementation of Na x GdF y O z :Yb/Er@TiO 2 hollow spheres in DSSCs imparted the light trapping due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…They have been extensively utilized in bioimaging, photodynamic therapy, lighting, lasing, optical communications, and potential 3D display . Recent studies have also shown that proper hybridization of UCNPs with perovskites can increase the energy conversion efficiency of solar light . Moreover, the distinctive characteristics of UCNPs, such as large anti‐Stokes shift, sharp absorption and emission band, no photobleaching, no photoblinking, and stable inorganic chemical composition, have also made them perfect candidates for special applications such as thermal imaging, night vision telescope, and remote distance measurement .…”
Section: Introductionmentioning
confidence: 99%
“…They have been extensively utilized in bioimaging, photodynamic therapy, lighting, lasing, optical communications, and potential 3D display . Recent studies have also shown that proper hybridization of UCNPs with perovskites can increase the energy conversion efficiency of solar light . Moreover, the distinctive characteristics of UCNPs, such as large anti‐Stokes shift, sharp absorption and emission band, no photobleaching, no photoblinking, and stable inorganic chemical composition, have also made them perfect candidates for special applications such as thermal imaging, night vision telescope, and remote distance measurement .…”
Section: Introductionmentioning
confidence: 99%
“…Hollow structured materials, which have large surface areas and complex inner structures can enhance dye loading, light harvesting efficiency and achieve much higher energy conversion efficiency . The upconverting emission profile of multifunctional Na x GdF y O z :Yb 3+ /Er 3+ /TiO 2 hollow spheres overlapping with the absorption spectra of N719 dyes molecules acted as an extremely broadband antenna system . The overall solar energy trapping efficiency was dramatically enhanced as a result of the light reflection of the composite hollow spheres and the overall broadening of the absorption spectrum.…”
Section: Applications Of Lphssmentioning
confidence: 99%
“…[18] Theb ilayerstructured photoanode,c omposed of small NPs and large NRs,c an lead to strong light scattering,p rovide as ufficient surface area for dye loading,a nd thus outperform TiO 2 NPsbased DSSCs. [19,20] In addition, the top layer consisting of YYEOF NRs can convert the NIR light into visible light to utilizet he solar spectrum more efficiently.A tt he same time, short distances between the N-719 dye and the top layer TiO 2 /YYEOF can ensure effective electron transfer between them. Figure 1s hows schematic structures of photoanodes based on TiO 2 /YYEOF ( Figure 1a)and pure TiO 2 films (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%